Reflections on Action Research Roles, Networks and Implications in English Language Teaching - Puengpipattrakul, Walaipun (Kasetsart Journal of Social Sciences, 2011)
This paper aims to reflect on what and how the author perceives action research is and will be in future. To be a good practitioner on conducting action research, a researcher needs to take its roles, relevant research variables and the guiding processes in conducting action research into account. With the special features of the research processes, they empower a researcher to reflect on or judge if each step can be pursued or flexibly re-taken. Moreover, since the author perceived the feasibility of conducting the action research networks through the varied topics of research proposals among nations from the SEAMEO RELC action research course, the implications to action research collaboration is thus supposed to be promoted and suggested as one of the possible solutions to research barriers in the paper.